2020
DOI: 10.1371/journal.pone.0227340
|View full text |Cite
|
Sign up to set email alerts
|

Effects of CK2β subunit down-regulation on Akt signalling in HK-2 renal cells

Abstract: The PI3K/Akt pathway is interconnected to protein kinase CK2, which directly phosphorylates Akt1 at S129. We have previously found that, in HK-2 renal cells, downregulation of the CK2 regulatory subunit β (shCK2β cells) reduces S129 Akt phosphorylation. Here, we investigated in more details how the different CK2 isoforms impact on Akt and other signaling pathways.We found that all CK2 isoforms phosphorylate S129 in vitro, independently of CK2β. However, in HK-2 cells the dependence on CK2β was confirmed by res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 59 publications
1
13
0
Order By: Relevance
“…In particular, T202/Y204 pERK1/2 sites have been shown to be to be affected indirectly by CK2 (Olsen et al 2012;Ritt et al 2007). We do not observe changes in T202/Y204 pERK1/2 site phosphorylation, confirming data by others which showed that knockdown or inhibition of CK2 did not alter pT202/pY204 ERK in Hela and renal HK-2 cells (Alcaraz et al 2020;Plotnikov et al 2011). Our data in patient cell lines suggest that typical signaling pathways in immortalized cells, may not be adequate for the assessment of CK2α activity in OCNDS-patient fibroblasts.…”
Section: Ck2α Activity Changessupporting
confidence: 76%
See 2 more Smart Citations
“…In particular, T202/Y204 pERK1/2 sites have been shown to be to be affected indirectly by CK2 (Olsen et al 2012;Ritt et al 2007). We do not observe changes in T202/Y204 pERK1/2 site phosphorylation, confirming data by others which showed that knockdown or inhibition of CK2 did not alter pT202/pY204 ERK in Hela and renal HK-2 cells (Alcaraz et al 2020;Plotnikov et al 2011). Our data in patient cell lines suggest that typical signaling pathways in immortalized cells, may not be adequate for the assessment of CK2α activity in OCNDS-patient fibroblasts.…”
Section: Ck2α Activity Changessupporting
confidence: 76%
“…We tested pS129Akt, a substrate for CK2 in several immortalized cell lines. Neither was pS473 Akt affected, a site which was shown to be downregulated upon CK2 inhibition of knockdown in Jurkat and HK-2 renal cells (Alcaraz et al 2020;Di Maira et al 2005). This phosphosite was not reduced in patient fibroblasts, in line with findings in CK2α knockout embryos.…”
Section: Ck2α Activity Changesmentioning
confidence: 96%
See 1 more Smart Citation
“…VHL [12,13], VEGF (vascular endothelial growth factor [14]), CAIX (carbonic anhydrase IX [15]), PTEN [15], CR1 (complement C3b/C4b receptor 1 [16]), MERTK (MER proto-oncogene tyrosine kinase [17]), PIK3CA (phosphatidylinositol-4,5-bisphosphate 3-kinase catalytic subunit alpha [18]), and AKT1 (AKT serine/threonine kinase 1 [19]) are among the most popular KC biomarkers. The PI3K/Akt pathway, one that is altered in several cancers, has been evaluated as a potential target for KC therapy [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…PTEN [15], CR1 (complement C3b/C4b receptor 1, [16]), MERTK (MER proto-oncogene tyrosine kinase [17]), PIK3CA (phosphatidylinositol-4,5-bisphosphate 3-kinase catalytic subunit alpha [18]) and AKT1 (AKT serine/threonine kinase 1 [19]) are among the most popular KC biomarkers. The PI3K/Akt pathway, one that is altered in several cancers, has been evaluated as a potential target for therapies [20].…”
Section: Introductionmentioning
confidence: 99%